1997
DOI: 10.1097/00005373-199705001-00011
|View full text |Cite
|
Sign up to set email alerts
|

Individual Patient Cohort Analysis of the Efficacy of Hypertonic Saline/Dextran in Patients with Traumatic Brain Injury and Hypotension

Abstract: Patients who have traumatic brain injuries in the presence of hypotension and receive HSD are about twice as likely to survive as those who receive standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(101 citation statements)
references
References 12 publications
2
92
1
6
Order By: Relevance
“…[16][17][18][19][20][21] All reviews posed a different clinical question and used different inclusion criteria. One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20][21] All reviews posed a different clinical question and used different inclusion criteria. One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] All reviews posed a different clinical question and used different inclusion criteria. One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline. 16 With regards to the five systematic reviews evaluating intracranial pressure management, they identified a reduction in intracranial pressure [16][17][18][19][20] associated with hypertonic saline solution, in contrast with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found improved systolic blood pressure on arrival to the emergency room. In 1997, Wade et al [58] performed a cohort analysis of patient data from previous prospective, randomized doubleblinded trials that evaluated the use of hypertonic saline/ dextran (HSD) solution in patients who had a traumatic brain injury (TBI). They found patients with TBI who had received the hypertonic saline/dextran solution were twice as likely to survive as those who received standard care.…”
Section: Pros and Cons Of Hyperosmolar Therapymentioning
confidence: 99%
“…17 In clinical trials, the beneficial effects of HSS during hemorrhagic shock in the presence of intracranial hypertension associated with systemic hypotension have been noted. 18,19 Increasing evidence suggests important advantages in HSS resuscitation, namely, reduction in postresuscitation complications such as renal failure, coagulopathies, and acute respiratory distress syndrome, possibly by modulation of the systemic inflammatory response. [20][21][22] The findings that HSS induces favorable effects on both systemic and cerebral hemodynamics in laboratory and clinical settings of IH suggest a potential use of this solution during OLT for FHF.…”
Section: Introductionmentioning
confidence: 99%